The Utility of Immature Granulocyte Count and Percentage on the Prediction of Acute Appendicitis in the Suspected Acute Appendicitis According to the Alvarado Scoring System: A Retrospective Cohort Study - Güler, Özlem; Bozan, Mehmet Buğra; Alkan Baylan, Filiz; Öter, Serdar (Turkish Journal of Gastroenterology, 2022)
Background: This study aimed to investigate the utility of immature granulocyte count and percentage on the prediction of suspected acute appendicitis according to the Alvarado scoring system and its effect on the need for computed tomography scanning. Methods: Adult patients who had an Alvarado scoring system between 4 and 7 with the first imaging technique computed tomography were included and retrospectively analyzed. The immature granulocyte count and granulocyte percentage were obtained from the blood samples taken at the time of the patient’s first admission to the hospital. Results: A total of 652 patients were evaluated and 186 patients were included in the study. Acute appendicitis was not detected in computed tomography imaging of 121 (65%) patients (group N) and detected in 65 (35%) patients (group P). The mean immature granulocyte percentage in group N and group P were 0.314 ± 0.188 (0.00-1.40) and 0.364 ± 0.205 (0.05-1.00), respectively. The mean immature granulocyte percentage was similar between groups (P = .095). The mean immature granulocyte count was 33 ± 46/μL (0-50) in group N and 60 ± 85/μL (10-690) in group P. Immature granulocyte count was significantly higher in group P (P = .005). Univariate analysis results revealed that age and immature granulocyte percentage were not predictive factors for the presence of acute appen- dicitis in suspected cases (P > .05). On the other hand white blood cell, neutrophil–lymphocyte ratio, C-reactive protein, and immature granulocyte count were determined as predictive factors in univariate analysis and multivariate analysis. Receiver operating character- istic curve analysis of preoperative immature granulocyte percentage and immature granulocyte count values in the diagnosis of acute appendicitis: the cut-off value of immature granulocyte percentage was ≥0.35 and its sensitivity, specificity, positive predictive value, and negative predictive value were 44.1%, 72.1%, 71.1%, and 41.5%, respectively (area under the curve: 0.588; CI: 0.484-0.682). The cut-off value of immature granulocyte count was ≥35/μL and its sensitivity, specificity, positive predictive value, and negative predictive value were 66.1%, 73.6%, 71.9%, and 67.7%, respectively (area under the curve: 0.743; CI: 0.659-0.827) Conclusion: Immature granulocyte count is a predictive factor for acute appendicitis in patients with the middle-risk group according to the Alvarado score and may be useful for the selective use of tomography. Cite this article as: Güler Ö, Bozan MB, Alkan Baylan F, Öter S. The utility of immature granulocyte count and percentage on the prediction of acute appendicitis in the suspected acute appendicitis according to the alvarado scoring system: A retrospective cohort study. Turk J Gastroenterol. 2022;33(10):891-898.